PENGARUH PEMBERIAN VITAMIN C DAN E TERHADAP GAMBARAN HISTOLOGIS GINJAL MENCIT (Mus musculus L.) YANG DIPAJANKAN MONOSODIUM GLUTAMAT (MSG) - Zulfiani Zulfi; Syafruddin Ilyas; Salomo Hutahaean (Saintia Biologi, 2013)
The aim of this research is to study the effect of vitamin C and E on kidney microstructure of mouse exposed to monosodium glutamate for 30 days. This research used complete randomized design which consisted of 6 treatments and 5 replications. The control consisted of K-, and K+ (castor oil 0.3 ml). The treatments were MSG 4 mg/g BW, P1 (only MSG), P2 (MSG plus vitamin C 0.26 mg/g BW), P3 (MSG plus vitamin E 0.026 mg/g BW) and P4 (MSG plus vitamin C and E). After treatments were completed, the mice were sacrificed by cervical dislocation, and kidney tissue section was prepared by the paraffin method and stained with Haematoxylin and Eosin staining. Microstructure damage of kidneys showed a significant difference between control and treatments. In P1, the proximal tubule damage was 69.95%±5 and in P4 was 47.22%±3. In summary MSG can cause damage in the form of a narrowing of the lumen of the proximal tubules of the kidney. A combination of vitamins C and E can reduce the effect of MSG on the kidney. Keywords: kidney, Monosodium glutamat (MSG), Vit C, Vit E.